Implementation of Pseudo-Coloring Technique on Thermal - Jorge, Loay; Al-Saadi, Aws (Iraqi Journal of Science, 2025)
The present investigation is concerned with measuring the effects of applying pseudo-celor technique on the ther nal images. In this study, therinal images of different scenes were tested the thermal drages are preduced using (Argus Falcon thermal camera from Raytheon Company) with waveband (3-5 & 8-12 micron): Pseudo coloring technique was adopted to make thermal images more perceivable and understandable. Two methods for image coloring (intensity slicing and color shading) were considered with twe kinds of corners distributions funiform and non